Agenda setting and socially contentious policies: Ethiopia's 2005 reform of its law on abortion - Sarah Jane Holcombe; Saba Kidanemariam Gebru (BMC, 2022)
Plain language summary Globally, deaths of women due to unsafe abortion remain high. However, few countries have changed their laws to allow safer, legal abortion. In 2005, Ethiopia reformed its law to permit women to obtain an abortion for a significantly greater number of reasons, and this reform has resulted in a real expansion of women's access to services. This retrospective case study uses information from interviews with 54 people involved in Ethiopia's reform and from government and research documents to see whether explanations of the reform that focus on the roles of national actors versus on the roles of external actors and influences better explain how Ethiopia's reform took place. This study finds that national actors and processes were most central to Ethiopia's reform. In particular, a ruling party open to reform, the work of the women's movement and of reproductive health nongovernmental organizations, the ability to take advantage of political events, and the collaborative relationship between government and nongovernmental organizations all supported reform. At the time, many major external actors were either against the reform (the U.S. government) or stayed neutral. Findings can help those seeking to understand or plan policy reform efforts in other sub-Saharan Africa countries.